The yeast p24 complex regulates GPI-anchored protein transport and quality control by monitoring anchor remodeling - Castillon, Guillaume A.; Aguilera-Romero, Auxiliadora; Manzano-Lopez, Javier; Epstein, Sharon; Kajiwara, Kentaro; Funato, Kouichi; Watanabe, Reika; Riezman, Howard; Muñiz, Manuel (Molecular biology of the cell, 2011)
Glycosylphosphatidylinositol (GPI)-anchored proteins are secretory proteins that are attached to the cell surface of eukaryotic cells by a glycolipid moiety. Once GPI anchoring has occurred in the lumen of the endoplasmic reticulum (ER), the structure of the lipid part on the GPI anchor undergoes a remodeling process prior to ER exit. In this study, we provide evidence suggesting that the yeast p24 complex, through binding specifically to GPI-anchored proteins in an anchor-dependent manner, plays a dual role in their selective trafficking. First, the p24 complex promotes efficient ER exit of remodeled GPI-anchored proteins after concentration by connecting them with the COPII coat and thus facilitates their incorporation into vesicles. Second, it retrieves escaped, unremodeled GPI-anchored proteins from the Golgi to the ER in COPI vesicles. Therefore the p24 complex, by sensing the status of the GPI anchor, regulates GPI-anchored protein intracellular transport and coordinates this with correct anchor remodeling.